2019
DOI: 10.1117/1.jbo.24.5.058001
|View full text |Cite
|
Sign up to set email alerts
|

Correction of hyperopia by intrastromal cutting and liquid filler injection

Abstract: Correction of hyperopia requires an increase of the refractive power by steepening of the corneal surface. Present refractive surgical techniques based on corneal ablation (LASIK) or intrastromal lenticule extraction (SMILE) are problematic due to epithelial regrowth. Recently, it was shown that correction of low hyperopia can be achieved by implanting intracorneal inlays or allogeneic lenticules. We demonstrate a steepening of the anterior corneal surface after injection of a transparent, liquid filler materi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 48 publications
0
7
0
Order By: Relevance
“…Other groups have tried to use a peripheral corneal gel injection to demonstrate myopia correction 13 and a pilot in vitro study in pig eyes demonstrated the feasibility of the central approach for hyperopia. 14 Analogous to the previous studies, which used firm corneal extension materials, a change in both the anterior and posterior surfaces was observed to correct hyperopia. This study reports the first systematic evaluation of refractive changes after filler injection in 120 rabbit eyes and provides a quantitative analysis of the achieved surgical results and demonstrates the adjustability of the approach.…”
mentioning
confidence: 68%
“…Other groups have tried to use a peripheral corneal gel injection to demonstrate myopia correction 13 and a pilot in vitro study in pig eyes demonstrated the feasibility of the central approach for hyperopia. 14 Analogous to the previous studies, which used firm corneal extension materials, a change in both the anterior and posterior surfaces was observed to correct hyperopia. This study reports the first systematic evaluation of refractive changes after filler injection in 120 rabbit eyes and provides a quantitative analysis of the achieved surgical results and demonstrates the adjustability of the approach.…”
mentioning
confidence: 68%
“…The increased precision and reduction in mechanical side effects in intrastromal cutting by the use of a vortex beam make this a promising approach for flap cutting in LASIK 4 and intrastromal pocket dissection for hyperopia correction 13,14 and offers even greater potential for improving SMILE. 10 In SMILE, a small lenticule is dissected and removed through a small side cut to achieve refractive correction in one step.…”
Section: Potential Improvements Of Refractive Surgery By Focus Shapingmentioning
confidence: 99%
“…Recently, a novel approach for hyperopia correction based on dissection of an intrastromal pocket followed by the injection of a biocompatible filler material has been introduced. 13,14 Despite more than 20 years of experience with LASIK and SMILE, there is still room for improvement with regard to efficiency, precision, and safety. Significant improvements can be achieved by addressing the key step of the refractive laser procedure: intrastromal dissection.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A previous ex vivo study showed that corneal filler injection is feasible for correcting hyperopia. 17 The following ex vivo pilot study explores the principle of corneal filler injection to establish corneal bifocality to correct presbyopia in an individual and adjustable manner.…”
Section: Introductionmentioning
confidence: 99%